Designation of a neotype for the kyphosid fish Kyphosus sectatrix (Linnaeus, 1758) - Gilbert, Carter R. (Zootaxa, 2015)
Several major systematic papers have recently been published on the perciform fish family Kyphosidae. One is a world revision of the family by Knudsen and Clements (2013), based largely on information summarized from an unpublished molecular phylogenetic analysis, supplemented by meristic and morphometric data. The second, by Sakai and Nakabo (2014), is a review of the genus Kyphosus from the Atlantic and eastern Pacific oceans only, based solely on conventional morphological and meristic information. The two papers include disagreements regarding identifications of two jointly examined specimens, erroneous or misleading information relative to types and type terminology, and conflicting meristic data. All of these have important taxonomic and nomenclatural implications, especially as regards Kyphosus sectatrix. Finally, the two studies were conducted completely independent of one another, and this is reflected both in the treatment of species and in certain of the respective conclusions.